Diffuse Large B-Cell Lymphoma of the Frontal Sinus Presenting as a Pott Puffy Tumor: Case Report - Khan, Nickalus R.; Lakičević, Goran; Callihan, Thomas R.; Burruss, George; Arnautović, Kenan (Journal of Neurological Surgery Reports, 2015)
Objective Sinonasal non-Hodgkin lymphoma (NHL) is a very rare condition. NHL located specifically in the frontal sinus is even rarer with only 14 cases in the literature reported to date. A unique case of diffuse large B-cell lymphoma of the frontal sinus that presented first and was treated as suspected Pott puffy tumor is presented along with a review of the literature.Case Report A 69-year-old white man with a history of sinusitis and two recent endoscopic sinus surgeries presented with enlargement of his right forehead. Computed tomography and magnetic resonance images revealed a dense opacification of the frontal sinus bilaterally, thickening and enhancement of the dura mater behind the right frontal sinus, and local osteomyelitis-like lytic bone changes. A bifrontal craniotomy was performed. Radical exoneration of the frontal sinus, copious antibiotic-impregnated irrigation after culture swabs, and resection of presumed granulation tissue was performed. Culture swabs remained negative, but histopathology revealed diffuse large B-cell lymphoma. Subsequent chemotherapy was administered.Conclusion Sinonasal NHL is very rare but can occur in the frontal sinus and may present as a suspected Pott puffy tumor. A high clinical suspicion is necessary for early diagnosis and treatment.
Keywords: diffuse large B-cell lymphoma; frontal sinus; case report; Pott puffy tumor